Analisis Kebiasaan Konsumsi Junk Food Di Kalangan Mahasiswa PGSD - Mufthia Urfa; Jesi Alexander Alim; Zakiah Ulya (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to analyze junk food consumption habits among students in the Elementary School Teacher Education Program (PGSD), focusing on consumption patterns, preferences, triggering situations, and their impacts on health and productivity. Employing a quantitative descriptive approach, data were collected through closed-ended questionnaires from 30 female PGSD students from the 2023 cohort, most of whom live in boarding houses (kosan). Frequency and percentage analysis revealed that 63.3% of respondents consume junk food 1-2 times per week, primarily at night (66.7%), with a main preference for instant processed foods such as instant noodles (63.3%). The dominant motivational factor is convenience (73.3%), while the primary triggering situation is limited time for cooking (76.7%). The impacts are moderate: 53.3% felt moderately affected on health, 46.7% reported minimal influence on study concentration, and 40% experienced no impact on productivity. These findings align with the literature on busy student lifestyles, emphasizing the need for nutritional education interventions to shape healthy role models for future teachers. This study recommends enhancing nutritional awareness through workshops or campaigns in the campus environment to encourage PGSD students to adopt healthy eating patterns and serve as role models for future generations.